Pembuatan Pembungkus Minuman Instan Berbahan Dasar Edible Film Dari Pektin Kulit Pisang Cavendish (Musa paradisiaca var. Sapientum) - romadhoni, milza; Satrio Kanugrahan Wahyu; Giesty Trienita S.Pd; Agus Widayoko (Jurnal Integrasi Sains dan Quran, 2024)
Indonesia is a country that is experiencing development in the industrial sector, especially in the field of instant drink packaging. The high level of instant drink consumption causes an increase in the amount of plastic waste. One of the biggest contributors to plastic waste is instant drink packaging. According to data from the Ministry of Environment and Forestry (KLHK), every minute one million plastics are used and the other 15% are only used once, then simply thrown into the environment. One alternative to replace plastic as packaging for instant drinks is edible film. Edible film is a thin layer that covers food that is suitable for consumption, and can be degraded by nature. Cavendish banana peel (Musa paradisiaca var. Sapientum) has the potential to be used as a base material for edible films because it has a high starch content and an average carbohydrate content of 3.96%, fat content of 1.68% and protein content of 0.64%. This research uses a quantitative descriptive method with a focus on making edible film as a substitute for instant drink packaging made from plastic which aims to reduce levels of plastic waste. The addition of sorbitol significantly increases the elongation and attractiveness of edible film which will later be used as packaging material for instant drinks. Tests carried out in this research include organoleptic tests, thickness tests and pull power tests. Based on the tests that have been carried out, this research has succeeded in making beverage wrappers that are easily degradable